Introducing Chaplaincy to Japanese Society - Kasai, Kenta (Journal of Religion in Japan, 2016)
This paper examines the meaning of the introduction of Clinical Pastoral Education (CPE) to Japan, as an example of one of the religious activities accepted in public space in a secular Japanese society. For over half a century, Christian clerics have tried to introduce the idea of chaplaincy to Japan, and Buddhists have attempted to develop a Buddhist form of hospice palliative care. The Japan Society for Spiritual Care was established in 2007 and began an accreditation process of ecumenically designed “spiritual caregivers,” bringing interested parties together in Japan for education, peer support, and continuous training in spiritual care. The outpouring of national grief in response to accidents or natural disasters encouraged sponsors to create CPE training institutions at some universities. Challenging the Japanese understanding of the separation of religion and state, the introduction of chaplaincy can be seen as a case of religious practice that is accepted in public space.